Comparative efficacy of conventional pap smear and liquid based cytology for screening of cervical cancer in women of reproductive age group in a tertiary care centre in rural Madhya Pradesh - Shambhavi; Suresh Kumar Sutrakar; Lokesh Tripathi; Parul Singh Rajpoot; Priyanka Agrawal; Uday Raj Singh; Jagannath Jatav; Deepti Tiwari; Pushpkunjika Sharma (Asian Journal of Medical Sciences, 2025)
Background: Cervical cancer poses a significant public health challenge, emphasizing the need for effective screening strategies for early detection. Conventional Pap smear (CPS) has been the standard screening tool for decades, while liquid-based cytology (LBC) was developed to overcome its limitations. This study compares the efficacy of CPS and LBC in detecting cervical neoplastic lesions. Aims and Objectives: To determine and compare the efficacy of CPS and LBC as screening tools for early detection of cervical neoplastic lesions in a tertiary care setting. Materials and Methods: A prospective observational study was conducted on 240 women aged 18 years and above from August 2022 to August 2023. CPS, LBC (Ezyprep™), and colposcopy-guided biopsies were utilized, with histopathology as the gold standard. Statistical analysis involved sensitivity, specificity, and receiver operating characteristic curves. Results: CPS showed a sensitivity of 59.62%, specificity of 94.19%, and sample adequacy of 93.3%, while LBC exhibited higher sensitivity (89.09%), comparable specificity (91.43%), and better sample adequacy (95.8%). The area under the curve for LBC (0.908) was significantly higher than CPS (0.735). LBC identified more true positives (49 vs. 31) and fewer false negatives (6 vs. 21). Conclusion: LBC demonstrated superior sensitivity, sample adequacy, and diagnostic accuracy, making it the recommended screening tool for high-risk populations.